1992
DOI: 10.1002/hlca.19920750417
|View full text |Cite
|
Sign up to set email alerts
|

Base Hydrolysis of Pentaaminecobalt(III) Complexes: The [CoX(dien) (dapo)]n+ system. Part 2. Structure and reactivity of the pentacoordinate intermediate

Abstract: Base hydrolysis of optically pure mer-exo(H)-and mer-endo (H)-[CoCl(dien)(dapo)]*+ (A and B (X = CI), resp.; dien = N-(2-aminoethyl)ethane-1,2-diamine; dapo = 1,3-diaminopropan-2-01, koH = (1.13 i 0.09). 10' (A (X = CI)), koH = (1.18 * 0.1 I ) . 105~vr1s-l (B (X = Cl)); I = 1 . 0~ (NdC1O4 or NaN,), T = 298 K) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…that the reasons given in 141 for the high reactivity of the structurally similar rner-[CoX(dien)(tn)l"+ ion might not be generally applicable, and that they might only be coincidental with our results [5]. [7] and of the mer-exo(H)-and mer-endo(H)hydroxo and -aqua complexes A and B (X = OH and H,O, resp. ), respectively, [8] is given in the following papers.…”
Section: Hci) Yields Mer-exo(h)- Mer-endo(h)- Unsym+zc-exo(oh)- Anmentioning
confidence: 51%
See 2 more Smart Citations
“…that the reasons given in 141 for the high reactivity of the structurally similar rner-[CoX(dien)(tn)l"+ ion might not be generally applicable, and that they might only be coincidental with our results [5]. [7] and of the mer-exo(H)-and mer-endo(H)hydroxo and -aqua complexes A and B (X = OH and H,O, resp. ), respectively, [8] is given in the following papers.…”
Section: Hci) Yields Mer-exo(h)- Mer-endo(h)- Unsym+zc-exo(oh)- Anmentioning
confidence: 51%
“…Essentially the same procedure was used to produce A(CIO,), (X = Cl) from the unsym-Sac-endo (OH)-isomer D. However, the initial base-hydrolysis step is much faster [7], and a reaction time of 1 min was sufficient. The final yield ofA(CIO,), (X = CI) was low (ca.…”
Section: Unsym-fac-endo(uh)unsym-fac-endo(uh)-~[co(diienj(dupo)/2/p-mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, base hydrolysis is practically as necessarily so. [12,23] It was therefore repeatedly concluded slow as in the case of 2. This may suggest that the rate at that the differences in the rate of base hydrolysis are mainly which cobalt(III) complexes of the type Co'N 5 'Cl 2ϩ follow governed by the lability of the conjugate base rather than the D cb mechanism will also be affected by the symmetry by differences in proton labilities of the parent complex.…”
Section: Kinetics Of Base Hydrolysismentioning
confidence: 96%
“…[20] The observed ratio for k OH (I ϭ 0.1 )/k OH (I ϭ 1.0 ) ϭ 2.4 is in accord with the averaged value k OH (I ϭ balt(III) complexes. [9] It has been shown that anion competition experiments [22,23] and the determination of reaction volume profiles [24] can provide experimental evidence for the validity of the commonly accepted D cb mechanism. In order to substantiate the operation of the D cb mechanism for the base hydrolysis of 2, experiments at different temperatures (see Table 4) and pressures (see Figure 5) were carried out.…”
Section: Kinetics Of Base Hydrolysismentioning
confidence: 97%